Shrimp disease investigation and culture strategies in Bagerhat district, Bangladesh - Shabuj, Md Azharul Islam; Bairagi, Tonusree; Asif, Abdulla Al; Faruq, Omar; Bari, Md Rafiqul; Neowajh, Md Sharif (Asian Journal of Medical and Biological Research, 2016)
The present study was conducted in three upazilla (Bagerhatsadar, Fakirhat and Rampaul) to investigate the shrimp diseases and culture strategies of Bagerhat district in 2012. Post larvae (PL-13/21) from hatchery and natural were used to stock in the study area. The highest mean stocking density was recorded in the ghers of Rampaul (16796±7729.69 PL/ha), where the maximum survival rate was also found (63.00±11.52 %). The highest dose of lime was recorded as 302.58±50.92 kg/ha at Bagerhat sadar; cowdung was recorded as 605.16±118.46 kg/ha at Fakirhat upazilla and urea was recorded as 29.02±5.84 kg/ha (Bagerhat sadar) respectively. The maximum doses of MP and TSP were recorded as 34.58±4.51 kg/ha at Bagerhat sadar and Fakirhat and 27.79±3.71 kg/ha at Bagerhat sadar respectively. No supplementary feed were fed to shrimp, in where culture dependent on natural foods. The highest shrimp production was found in Fakirhat upazila (667±307.05 kg/ha) and the lowest production was in Rampaul upazilla (497±268.97 kg/ha). Sudden change of pH , low dissolved o2 levels, salinity variations, nutritional deficiency and other environmental changes causes yellow head viral disease (YHD), white spot syndrome viral (WSSV), vibriosis, fusarium and protozoan were recorded during the experimental period. Asian J. Med. Biol. Res. December 2015, 1(3): 545-552